Evaluating the surface circulation in the Ebro delta (northeastern Spain) with quality-controlled high-frequency radar measurements - Lorente, Pablo; Piedracoba, Silvia; Soto-Navarro, Francisco Javier; Álvarez-Fanjul, Enrique (European Geosciences Union, 2015)
The Ebro River delta is a relevant marine protected area in the western Mediterranean. In order to promote the conservation of its ecosystem and support operational decision making in this sensitive area, a three-site standard-range (13.5 MHz) CODAR SeaSonde high-frequency (HF) radar was deployed in December 2013. The main goal of this work is to explore basic features of the sea surface circulation in the Ebro deltaic region as derived from reliable HF radar surface current measurements. A combined quality control methodology is applied: firstly, 1-year long (2014) real-time web monitoring of nonvelocity-based diagnostic parameters is conducted to infer both radar site status and HF radar system performance. The signal-to-noise ratio at the monopole exhibited a consistent monthly evolution, although some abrupt decreases (below 10 dB) impacted negatively on the spatiotemporal coverage of total current vectors. It seemed to be sporadic episodes since radar site overall performance was found to be robust during 2014. Secondly, a validation of HF radar data with independent in situ observations from a moored current meter was attempted for May–October 2014. The accuracy assessment of radial and total vectors revealed a consistently high agreement. The directional accuracy of the HF radar was rated at better than 8°. The correlation coefficient and root mean square error (RMSE) values emerged in the ranges [0.58–0.83] and [4.02–18.31] cm s−1, respectively. The analysis of the monthly averaged current maps for 2014 showed that the HF radar properly represented basic oceanographic features previously reported, namely, the predominant southwestward flow, the coastal clockwise eddy confined south of the Ebro delta mouth, or the Ebro River impulsive-type freshwater discharge. The EOF analysis related the flow response to local wind forcing and confirmed that the surface current field evolved in space and time according to three significantly dominant modes of variability.
Keywords: Ebro (Cuenca hidrográfica); HF Radar; Ebro Delta; Marine protected areas; Quality control; Surface circulation